049 The Effect of Obstructive Sleep Apnea on Emotional Memory Consolidation. (3rd May 2021) - Cunningham, Tony; Kishore, Divya; Guo, Mengshuang; Igue, Moroke; Malhotra, Atul; Stickgold, Robert; Djonlagic, Ina
Abstract: Introduction: A growing body of evidence suggests that sleep is critical for the processing and consolidation of emotional information into long-term memory. Previous research has indicated that emotional components of scenes particularly benefit from sleep in healthy groups, yet sleep dependent emotional memory processes remain unexplored in many clinical cohorts, including those with obstructive sleep apnea (OSA). Methods: In this study, a group of newly diagnosed OSA patients (n=26) and a matched group of healthy controls (n=24) encoded scenes with negative or neutral foreground objects placed on neutral backgrounds prior to a night of polysomnographically recorded sleep. In the morning, they completed a recognition test in which objects and backgrounds were presented separately and one at a time. Results: OSA patients have a deficit in both overall gist memory and the specific recognition memory for the scenes. Impairment of gist recognition was across all elements of the scenes, both negative and neutral objects and backgrounds [main effect of group: F(1, 48) = 13.5, p=0.001], while specific recognition impairment was exclusively found for negative objects [t(48)=2.0, p=0.05]. Across all participants, successful gist recognition correlated positively with sleep efficiency (p=0.001) and REM sleep (p=0.009), while successful specific memory recognition correlated only with REM sleep (p=0.004). Conclusion: Our findings indicate that fragmented sleep and reduced REM sleep, both hallmarks of OSA, significantly disrupt distinct memory processes for emotional content. Gist memory is universally impacted, while memory for specific details appears to have a greater deterioration for negative aspects of memories. These memory affects may have impacts on complex emotional processes, such as emotion regulation, and could contribute to the high comorbid depressive symptoms in OSA. Support (if any): The authors would like to thank the funding sources awarded to author ID for supporting this research: NIH grant # K23HL103850 and American Sleep Medicine Foundation grant #54-JF-10. Author TJC is currently funded by the Research Training Program in Sleep, Circadian and Respiratory Neurobiology (NIH T32 HL007901) through the Division of Sleep Medicine at Harvard Medical School and Brigham & Women's Hospital.